Investigation of crossed SAW fields by scanning acoustic force microscopy. - Behme, G; Hesjedal, T (2001)
We used multimode scanning acoustic force microscopy (SAFM) for studying noncollinearly propagating Rayleigh and Love wave fields. By analyzing torsion and bending movement of SAFM cantilever, normal and in-plane wave oscillation components are accessible. The SAFM principle is the down-conversion of surface oscillations into cantilever vibrations caused by the nonlinearity of the tip-sample interaction. Through mixing of complementary oscillation components, phase velocities of crossed Rayleigh waves on GaAs and crossed Rayleigh and Love waves on the layered system SiO2/ST-cut quartz were obtained simultaneously. Now, it is possible to investigate elastic properties of submicron areas through multimode SAFM measurements. Finally, we present mixing experiments of four SAWs on GaAs and discuss the various influences on the measured SAFM amplitude and phase contrast.